Panel Data Nonparametric Estimation of Production Risk and Risk Preferences: An Application to Polish Dairy Farms - Tomasz Gerard Czekaj; Arne Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
We apply nonparametric panel data kernel regression to investigate production risk, out-put price uncertainty, and risk attitudes of Polish dairy farms based on a firm-level unbalanced panel data set that covers the period 2004–2010. We compare different model specifications and different approaches for obtaining firm-specific measures of risk attitudes. We found that Polish dairy farmers are risk averse regarding production risk and price uncertainty. According to our results, Polish dairy farmers perceive the production risk as being more significant than the risk related to output price uncertainty.
Keywords: C14; C23; D24; Q12; 330; production risk; price uncertainty; nonparametric econometrics; panel data; Polish dairy farms